EFFICACY OF LOCAL ANAESTHESIA IN REPAIR OF INGUINAL HERNIA - Rafiq, Muhammad Kashif; Sultan, Babar; Malik, Masood Akhtar; Khan, Khalid; Abbasi, Munir Ahmad; Khan, Khalid (Journal of Ayub Medical College Abbottabad, 2016)
Background: Local anaesthesia has been identified as the most favourable anaesthesia for elective inguinal hernia repair with respect to complication rate, cost effectiveness and overall patients’ satisfaction. This study was conducted to determine the efficacy of local anaesthesia in inguinal hernia in terms of pain relief, wound infection and hospital stay. Methods: In this randomized controlled trial (RCT), 60 patients with inguinal hernia were included at the General Surgical ’˜B’ Unit, Ayub Teaching Hospital Abbottabad. Results: The day-case rates were significantly higher when patients underwent surgery under LA compared to GA (82.6% versus 42.6%). The incidence of urinary retention was higher in the GA group (p<0.05). There were 17 (2.9%) re-admissions overall. The reasons for re-admission included haematoma (n=6), severe pain (n=4), infection (n=3), fainting (n=2) and urinary retention (n=2). Conclusion: This study demonstrates that local anaesthesia for inguinal hernia repair has better efficacy as compared to general anaesthesia. Keywords: General anaesthesia; local anaesthesia; inguinal hernia; Comparison